HIV Prevention Messages Targeting Young Latino Immigrant MSM. (17th April 2014) - Solorio, Rosa; Norton-Shelpuk, Pamela; Forehand, Mark; Martinez, Marcos; Aguirre, Joel
Abstract : Young Latino immigrant men who have sex with men (MSM) are at risk for HIV and for delayed diagnosis. A need exists to raise awareness about HIV prevention in this population, including the benefits of timely HIV testing. This project was developed through collaboration between University of WA researchers and Entre Hermanos, a community-based organization serving Latinos. Building from a community-based participatory research approach, the researchers developed a campaign that was executed by Activate Brands, based in Denver, Colorado. The authors (a) describe the development of HIV prevention messages through the integration of previously collected formative data; (b) describe the process of translating these messages into PSAs, including the application of a marketing strategy; (c) describe testing the PSAs within the Latino MSM community; and (c) determine a set of important factors to consider when developing HIV prevention messages for young Latino MSM who do not identify as gay.